Architectural plans for the ottoman civil buildings in Mascara city - Qarman, Abdul Qadir (The Algerian Historical Journal, 2026)
Civil architecture in Algeria during the Ottoman period was affected by the Ottoman architectural style, as many new architectural styles and elements were introduced into its plans, which were not known before. It also included all aspects of life in terms of the availability of political, social, health, economic and cultural conditions. Prof. Dr. Laraj Abdul Aziz, may God have mercy on him, discussed in several researches these models and schemes, especially religious and civil ones, This study aims to introduce the civilian buildings in the city of Mascara, and their architectural and artistic styles by comparing them with the installations of Algeria during the Ottoman period, where we finally reached the similarity of the civilian buildings in Mascara in their architectural and artistic styles with their counterparts in Algeria.